3+6x+15=-7x-2+3x

Simple and best practice solution for 3+6x+15=-7x-2+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+6x+15=-7x-2+3x equation:


Simplifying
3 + 6x + 15 = -7x + -2 + 3x

Reorder the terms:
3 + 15 + 6x = -7x + -2 + 3x

Combine like terms: 3 + 15 = 18
18 + 6x = -7x + -2 + 3x

Reorder the terms:
18 + 6x = -2 + -7x + 3x

Combine like terms: -7x + 3x = -4x
18 + 6x = -2 + -4x

Solving
18 + 6x = -2 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
18 + 6x + 4x = -2 + -4x + 4x

Combine like terms: 6x + 4x = 10x
18 + 10x = -2 + -4x + 4x

Combine like terms: -4x + 4x = 0
18 + 10x = -2 + 0
18 + 10x = -2

Add '-18' to each side of the equation.
18 + -18 + 10x = -2 + -18

Combine like terms: 18 + -18 = 0
0 + 10x = -2 + -18
10x = -2 + -18

Combine like terms: -2 + -18 = -20
10x = -20

Divide each side by '10'.
x = -2

Simplifying
x = -2

See similar equations:

| x^3+2x^2=200 | | -11/3=-7/6k-2/3k | | 6x+5-4x=8-x+9 | | 2x-2.5=10 | | 25+5(y+20)=3(y-1) | | 4x-1/x=0 | | -24x^2+21x+15=0 | | 8(x-5)-6=26x-190 | | -16-4x=8x-7 | | 7x-8+3x=5x-13 | | -16-4x=8-7 | | -0.5x-5=0 | | 56x+9=89-5x | | 3/x+2=7 | | [9-2(4-1)]= | | 4y-3=6y+21 | | 3x+3-12=-5 | | 48/2^3+25*(9-7) | | c=2x+18 | | -7/2x+1+31/2=8 | | x^3-5x=14 | | -4+0.33x=0 | | 8(x-5)-6=26x-90 | | 2x-5=2x-35 | | -5/2z-15 | | 5+2[9-2(4-1)]= | | 7(x+3)+4=-3(x-6)-9 | | 4x+18=4x-102 | | 4(2x-1)=(x+4) | | 7/3x+1/3x=5x+14/3+7/3x | | 20-0.5x=0 | | 7x^3-7= |

Equations solver categories